Listeners' and Performers' Shared Understanding of Jazz Improvisations - Schober, Michael F.; Spiro, Neta (Frontiers in Psychology, 2016)
This study explores the extent to which a large set of musically experienced listeners share understanding with a performing saxophone-piano duo, and with each other, of what happened in three improvisations on a jazz standard. In an online survey, 239 participants listened to audio recordings of three improvisations and rated their agreement with 24 specific statements that the performers and a jazz-expert commenting listener had made about them. Listeners endorsed statements that the performers had agreed upon significantly more than they endorsed statements that the performers had disagreed upon, even though the statements gave no indication of performers' levels of agreement. The findings show some support for a more-experienced-listeners-understand-more-like-performers hypothesis: Listeners with more jazz experience and with experience playing the performers' instruments endorsed the performers' statements more than did listeners with less jazz experience and experience on different instruments. The findings also strongly support a listeners-as-outsiders hypothesis: Listeners' ratings of the 24 statements were far more likely to cluster with the commenting listener's ratings than with either performer's. But the pattern was not universal; particular listeners even with similar musical backgrounds could interpret the same improvisations radically differently. The evidence demonstrates that it is possible for performers' interpretations to be shared with very few listeners, and that listeners’ interpretations about what happened in a musical performance can be far more different from performers’ interpretations than performers or other listeners might assume.